An introduction to financial markets and institutions - Burton, Maureen (M.E. Sharpe, 2010)
Completely revised and updated to include the ongoing financial crisis and the Obama administration's programs to combat it, this is the best available introductory textbook for an undergraduate course on Financial Markets and Institutions. It provides balanced coverage of theories, policies, and institutions in a conversational style that avoids complex models and mathematics, making it a student-friendly text with many unique teaching features. Financial crises, global competition, deregulation, technological innovation, and growing government oversight have significantly changed financial markets and institutions. The new edition of this text is designed to capture the ongoing changes, and to present an analytical framework that enables students to understand and anticipate changes in the financial system and accompanying changes in markets and institutions. The text includes Learning Objectives and end-of-chapter Key Words and Questions, and an online Instructor's Manual is available to adopters.